Influence of furrow width on the stability of titanium implants. A study in the rabbit - Patricia Miranda Burgos; Luiz Meirelles; Lars Sennerby (Ariesdue, 2011)
Aim: Previous rabbit studies demonstrated higher affinity for bone formation at implant threads with furrows to threads without furrows. The present animal study was undertaken to study the bone tissue response and stability of oxidized titanium implants with 80, 110 and 160 μm wide furrows added on one thread flank. Materials and methods: Ninety-six (96) threaded titanium implants, 3.75 mm in diameter and 7 mm long (TiUnite™, MKIII, Nobel Biocare AB, Gothenburg, Sweden), were manufactured with 70 μm deep and either 80 (S0), 110 (S1) or 160 (S2) μm wide furrows or no furrows (controls). The implants were installed in the distal femoral condyle and the tibial methaphysis of 12 rabbits. Six weeks later the implants were subjected to resonance frequency analysis (RFA) and removal torque (RTQ) tests, after ground sections were manufactured for light microscopy. Results: A significantly increased (22%) stability of S1 implants in femoral sites compared with control implants was found. RFA showed no significant differences between test and control implants. Histology revealed more frequent bone fill of furrows with decreased width in parallel with increased frequency of fracture of the bone at the furrow entrance as opposed to a separation at the interface. Conclusion: The present study demonstrated an increased and maximum rotational stability of oxidized titanium implants with a 110 μm wide furrow on one thread flank compared with control implants without a furrow. The observed increased stability can be explained by fracture of the bone at the entrance of the furrow as opposed to a separation at the interface as seen at the wider furrows and at control implants.